Hairy Root Cultures of Hypericum perforatum L.; A Promising Method for The High Scale Production of Hypericin - M Montazeri M (M.Sc.); M Azadbakht; H Najafi Zarrini; GhA NematZadeh; A Pakdin Parizi; A Davoodi (Institue of Medicinal Plants, ACECR, 2018)
Background: Biotechnologic methods are common for secondary metabolites production from the plants and other sources in pharmaceutical sciences. Hairy root cell lines as the biotechnologic method have been used for in vitro production of major plant metabolites. Objective: In this study, hairy roots of Hypericum Perforatum have been prepared using the seeds and bio transformed by bacteria. Finally, the hypericin have been producted by the hairy roots. Methods: First, the seeds have been incubated in the plant media to hairy roots produced. Then, the hairy roots have been dipped in Rhizobium rizogenes suspension for biotransformation of bacterial genes. Morphological and phytochemical features of hairy roots have been determined in order to select the H. perforatum genotypes with higher hypericin contents. The fresh and dry weight of ten lines clones were measured after 30 days. In addition to, methanolic extracts of final hairy roots have been prepared and hypericin has been isolated and assayed by High Performance Liquid Chromatography. Results: According to the observations, one of ten hairy root lines shows 75-fold higher hypericin content (339.27 ppm) compared to non-transformed H. perforatum (4.58 ppm) in the same of body weight of roots. The clone with the most content of hypericin had significant development of biomass of hairy roots and increase the hypericin production. Transformed clones were varied in morphology, growth, and metabolite productivity. Conclusion: The mentioned methods induce the production of hairy root secondary metabolites in high scale to improve the quality and the quantity of pharmaceutical compounds.